ISOLASI DAN KARAKTERISASI ISOLAT BAKTERI RESISTEN TEMBAGA DARI SUNGAI CISADANE - Wahyu Irawati; Candra Yulius Tahya (BERITA BIOLOGI, 2020)
The water quality of the Cisadane River, located in the industrial factory area, it is contaminated with copper, it is necessary to treat sewage. Biological wastewater treatment using bacteria is a more economical and effective method of removing copper from the environment than chemical methods. This study aims to isolate, identify, determine the level of resistance, and analyze the ability of bacteria to accumulate copper. Isolation was carried out by the spread method in Luria Bertani Agar medium containing CuSO4. Bacterial isolates were identified based on analysis of the 16S rDNA gene. The resistance level is determined based on the Minimum Inhibitory Concentration (MIC) value. The accumulation ability of copper was determined using an atomic absorption spectrophotometer. Six bacteria resistant to copper were isolated and identified as Pantoea agglomerans strain IrCis1, Klebsiella grimontii strain IrCis3, Klebsiella penumoniae strain IrCis4, Shigella flexneri strain IrCis5, Enterobacter cloacae strain IrCis6, and Enterobacter cloacae strain IrCis9 with MIC of 7 mM - 9 mM. Pantoea agglomerans strains IrCis1, Klebsiella grimontii strains IrCis3, Klebsiella pneumoniae strains IrCis4 can accumulate copper of 1,19 mg, 1,39 mg, and 0,92 mg, respectively, per gram of dry cell weight.